The Role of Religious Norms On Selecting The Islamic Bank - Hardius Usman (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
The aims of this study are to examine Muslim’s religious norms regarding to their belief on the law of the prohibition of bank interest, and to investigate the effect of religius norms on customers’ decision in using the Islamic banking services. This study employs natural experimental design with Analysis of Variance (ANOVA), and Pearson Chi-Square Test. The exploratory study also conducted to support the quantitative analysis. The results show that the religious norms among Muslims classified into two categories, i.e: traditional and contemporary group and the religious norm of the Muslim have significant affects on the decision in using the Islamic banks.DOI:10.15408/aiq.v7i1.1356